The familiar look. Conversation with Martin Belaunde Moreyra - Coello Pöhl, Tatiana (Mercurio Peruano, 2016)
Interview about family memories in which somme personality traits, and particular interests of Víctor Andrés Belaunde are revealed. The mark that left on him the teaching in the United States, his love for Peru, and his open and confident vision of Christianity and specifically about faith and tolerance. Belaunde considered that "the ideology and the sense of the Christian faith had to be manifested in the conduct of public men through an honest intellectual and economic performance; decorous and neat conduct in his personal life and, if possible, elegant in his external appearance". He lived his everyday life and his family environment in the same way he defended honesty and decency in his speeches.